Neuroprotective Effects of Ellagic Acid, Rutin and p-Coumaric Acid on Diabetic Neuropathy Rats - Z. Fazlin; T. Myo; D. Muhammad Fauzi; M. Resni; M. Noorzaid (Asian Journal of Medicine & Health Sciences, 2022)
Background: The peripheral nervous system has regenerative capability which mainly dependent on Schwann cells plasticity. The administration of phenolic compounds may reduce damage to the peripheral nerve due to diabetic peripheral neuropathy. Hence, this study was conducted to determine the neuroprotective effect of phenolic compounds on in vivo and in vitro models of diabetic neuropathy. Methods: Streptozotocin-induced diabetic rats were treated orally with ellagic acid (100 mg/kg), rutin (100 mg/kg), p-coumaric acid (100 mg/kg) and metformin (500 mg/kg), respectively. The control and diabetic groups were given 5% DMSO in 0.9% sodium chloride. After 28 days, fasting blood glucose was determined and the pancreas and sciatic nerves processed for H&E staining. ANOVA analysis was performed. p<0.01 was considered statistically significant. Results: No reduction in blood glucose level of the severely hyperglycaemic diabetic rats was observed following treatment with the phenolic compounds. However, they do show protective effect on the pancreatic islets of the diabetic rats. Slow progression of sciatic nerve damage was observed with a slight increase in Schwann cells proliferation. Conclusion: In conclusion, while reduction in blood glucose level was not observed, the phenolic compounds may have a neuroprotective effect by promoting pancreatic repair. Proliferation of Schwann cells may play a protective role in hyperglycaemia by protecting the peripheral nerve and promoting regeneration.